Pembuktian Strategi Pengarusutamaan Gender (PuG): Analisis Capaian Indeks Pemberdayaan Gender di Indonesia - Hasnidar Yuslin (Jurnal Ekonomi Dan Statistik Indonesia, 2021)
This study aims to prove the Gender Mainstreaming strategy which is analyzed from the achievements of the Gender Empowerment Index from 2010 to 2020. To prove the Gender Mainstreaming strategy, the author uses an index measurement approach from the indicators forming the Gender Empowerment Index which is then analyzed descriptively. It was found that the implementation of the Gender Mainstreaming strategy in Indonesia has not been optimal. The average achievement of the gender empowerment index from 2010 to 2020 was 71.39, which is still far from the perfect ratio of 100. Judging from its forming indicators, it was found that the representation of women in parliament from 2010 to 2020 was still below 30 percent, then women as the professional workforce are still growing at 40 percent which has not yet reached the 50 percent equality level, and the contribution of women's income has experienced an increasing trend which reflects that women have been included in the workforce, but the increase has been slow.